A systematic review on the metaverse-based blended English learning - Li, Ming; Yu, Zhonggen (Frontiers in Psychology, 2023)
Over the past two decades, various digital technologies have been applied to sustain higher education. As the latest emerging information technology, the metaverse has been a recurring theme to be considered as a new direction to promote blended English learning. This study aims to investigate metaverse-based blended English learning. Through a systematic review based on bibliographic and content analysis, the study attempts to integrate the evidence to generate a model that links the education-based metaverse. The metaverse platforms in which learners' academic success can be significantly enhanced due to a high degree of learner engagement in immersive virtual environments. In addition, the virtual learning experience is restricted by the degree of digital literacy at the same time. To improve instructors' and learners' digital literacy levels, necessary support is indispensable by educational institutions and designers of the metaverse platforms. Meanwhile, this study addresses potential challenges that may hinder sustaining metaverse-based blended English learning, and provides some suggestions based on the previous literature. In future research, we will keep updating and polishing the metaverse-based blended English learning research to provide more detailed guidance for researchers and educators.